Feeding habits of the crested porcupine Hystrix cristata L. 1758 (Mammalia, Rodentia) in a Mediterranean area of Central Italy. Issue 1 (1st January 2017) - Mori, E; Bozzi, R.; Laurenzi, A.
Abstract: Old World porcupines are widely recorded as being agricultural pests throughout their distribution range. Despite being legally protected in Italy, the crested porcupine Hystrix cristata is extensively poached for its meat as well as for complained crop damages. In this work, we analysed the diet of crested porcupines in a Mediterranean coastal area surrounded by agricultural patches. Feeding habits of this species were assessed throughout the year through faecal analysis. Underground vegetal organs were the staple of the diet of this large rodent in both cold and warm months. Fruits were consumed mainly in cold months (hard epicarp species, e.g. acorns and pine nuts). In warm months, agricultural products, e.g. sunflowers, cereals and watermelons, were mostly consumed. Patterns of food consumption are consistent with a study on habitat selection by crested porcupine within the same study area. According to this previous study, the Mediterranean â€œmacchiaâ€ represents a poor habitat in terms of food resources and it is selected only in cold months, when porcupines mainly feed on underground storage organs of woodland plants. During the summer, porcupines are forced to travel long distances to search for other food categories, e.g. cultivated species.